ANALISIS PENERAPAN PRINSIP 5C TERHADAP KREDIT MACET PADA PT. ADIRA DINAMIKA MULTIFINANCE TBK. MOBIL CABANG NANGKA PEKANBARU - Elvis Arisman L. T; Makhdalena Makhdalena; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is about the application of 5C principles (Character, Capacity, Capital, Collateral, Condition) to bad credit. Lending PT. Adira Multifinance Dynamics is inseparable from the risk of bad credit, for that it requires risk management that can minimize the level of losses that may arise by trying to examine the factors that cause the occurrence of bad credit. Thus researchers are interested in conducting this research. The purpose of this study was to analyze the application of 5C and the level of bad credit. The population of the study is customers who are included in the list of bad loans at PT. Adira Multifinance Dynamics. The type of data used in this study is primary data obtained from questionnaires and secondary, namely by listing customers who experience bad credit. The method of data analysis uses multiple regression. The results of the study show that the principle of applying 5C itself is often ignored in the process of applying for credit. Where, many found marketing that handles every customer often do data manipulation. And this is less prudent in a credit officer in terms of assessing credit applications.Key Words: Character, Capacity, Capital, Collateral, Condition, Bad credit.